J.J. Lorimer and his approach to writing the history of the Arabian Gulf - al-Qaisi, Alaa Ataallah Subeh (Al-Adab Journal, 2021)
This study examines the G.J. methodology. Lorimer writes the history of the Arabian Gulf, which has been very interested in the corridors of the British government, which commissioned the employee to gather information and knowledge of every small and large gulf in order to create a guide that British state employees living in the Gulf can refer to, to obtain the necessary information to facilitate their work in the region. In light of this, Lorimer did not adhere to the correct approach in scientific research, neutrality and objectivity is one of the indicators that weakened the evidence, as the evidence came from a purely British point of view, there was no indication that the British or Indian government had acted wrongly, and there was no criticism of the British staff and British political representatives, and we can say that it was more royal than the King.